Evaluation of the effectiveness of some local plant extracts in improving the quality of unsafe water consumed in developing countries - Konkobo, Frédéric Anderson; Savadogo, Paul Windinpsidi; Diao, Mamounata; Dakuyo, Roger; Dicko, Mamoudou Hama (Frontiers in Environmental Science, 2023)
This study highlights the possibility of using plant extracts as biocoagulants to replace aluminum sulfate in the process of raw water potabilization. For this purpose, nine plants were identified by an investigation and their effectiveness was evaluated in the laboratory by coagulation/flocculation on surface waters. Out of the nine plants identified, five extracts showed a very low coagulant activity in the reduction of water samples turbidity (maximum abatement of 1.03%): These were the seeds of Acacia nilotica, Adansonia digitata, Balanites aegyptiaca, Tamarindus indica and leaves of Capparis corymbosa. Two extracts showed an average activity, namely Aloe vera sap (20.7%) and Opuntia ficus indica sap (32.25%). Two other extracts which are Moringa oleifera seeds and Boscia senegelensis seeds, showed a very good activity (84.83% and 82.97%, respectively after 1 h of decantation). By fixing the optimal concentration of 1 g/L for the treatment with Moringa oleifera seeds, a water of 4.6 NTU was obtained after 2 h of decantation, which was about 98% of abatement. The treatment with Boscia senegelensis seeds also allowed us to obtain for 2.5 g/L a water of 4.9 NTU after 2 h of decantation. The combined action of Moringa and Boscia biocoagulants, and cactus and Aloe mucilages reduced the decanting time to 15 min. These two treatments induced a slight increase of the minerals initially present in the water and a reduction of almost 99% of the pathogenic microorganisms. Thus, Boscia senegelensis and Moringa oleifera seeds appear as very effective biocoagulants compared to aluminum sulfate, hence they constitute an alternative to the lack of access to drinking water especially for developing countries.